Customer satisfaction survey, menu development and HACCP training to improve the food service quality of canteens - Dwi Budiningsari; Siti Helmiyati; Setyo Utami Wisnusanti; Lily Arsanti Lestari; Sridanti Annissa Putie (Journal of Community Empowerment for Health, 2023)
Canteens are an important aspect of the food environment in providing healthy food and supporting good nutrition. The food service quality of the canteens could be improved by customer satisfaction and the food traffic light system survey. This aimed to measure customer satisfaction and the food traffic light system implemented in the canteen via surveys and identify the impact of menu development training as well as Hazard Analysis Critical Control Point (HACCP) training for canteen staff. The customer satisfaction and the food traffic light system survey were collected using an online form involving 1,022 and 49 respondents, respectively. The training was attended by 31 canteen staff. In addition to menu development training, we also conducted HACCP training. Menu development training included menu variation, creating new recipes, and a food traffic light system. A descriptive post-evaluation was conducted to evaluate the impact of the training. A 6-question survey assessed how well the canteen staff retained knowledge from the provided food safety training. The customer satisfaction survey obtained the mean score for each indicator: 3.48 for canteen hospitality, 3.43 for canteen cleanliness, 3.32 for food taste, 3.22 for menu variation, and 3.14 for food prices. The training was useful to increase food service and board quality and the canteen staff ’s healthy food knowledge. More than half of the customers sometimes checked the food traffic light label. They mostly considered energy the main important nutrition to consider before buying food. The results of HACCP training showed that all participants correctly answered more than half of the questions. The responses of surveyed staff members suggest that the training was useful in increasing food service quality as well as food safety knowledge and practices of canteen staff. The sustainability of training impacts should be evaluated to gain comprehensive evaluation and identify further interventions to improve the food quality of canteens. As a health-promoting university, a food traffic light system should be implemented in canteens at other faculties at Universitas Gadjah Mada.